Development of environmental education in Sarawak - Suliman Jamahari (Jabatan Perlindungan Hidupan Liar dan Taman Negara, 2014)
The Sarawak Forest Department is one of the agencies involved in carrying out Environmental Education in Sarawak. Both formal and non formal programs are conducted. Among the target groups are primary and secondary school children, trainee teachers, graduates in Diploma of Education and school leavers. The location for Environmental Education are in Bako national Park, Semenggok Wildlife Rehabilitation Center, Sebangkoi Recreation Park, Lambir Hills National Park, Similajau National Park and Sarawak Teacher Training College. In a year, not less than 1000 trainee teachers, 500 students and 1500 people (from the general public) take part in the Environmental Education program.